Social skills during the covid 19 pandemic in students of a national university in Lima - Chávez Colmenares , Daniel Angel (2024)
The health emergency characterised by the coronavirus (COVID-19) conditioned our social relations to limit any social contact. These necessary measures that we adopted to contain the virus affected university students, in the relationship of strengthening and deepening their social skills. This is why some authors defend the importance of practising and reinforcing these skills by developing their ability to value themselves, self-regulate, communicate and make assertive decisions, seeking innovative changes and encouraging personal growth in university students. The aim of this study is to determine the level of social skills of the students of the faculty of education in the university environment during the pandemic, by means of the analysis of results through a social skills questionnaire validated with Cronbach's Alpha statistical test. Therefore the results indicate that social skills are paramount for the success and integral development of university life as they allow to maintain a positive attitude, confident communication and determine the path towards a life plan.